Kanonizacija Nakajime Atsushija - Senica, Klemen (Primerjalna književnost, 2016)
The paper analyses a recent phenomenon in Japan in which some prominent literary historians, among them Sudo Naoto, are trying to identify the first Japanese postcolonial writer. Such an undertaking is considered quite problematic by the author because it could be put in the broader context of historical revisionism, which has been rampant in Japanese political and academic discourse over the last decades
Keywords: Nakajima, Atsushi, 1909-1942; japonska književnost; imperializem; postkolonializem; kolektivni spomin; zgodovinski revizionizem; Mikronezija